Pengembangan Bahan Ajar dengan Pendekatan Student Centered Learning (SCL) pada Materi Kultur Jaringan - Lubis, Jalilah Azizah; Ginting, Nurmaini (Jurnal Pendidikan Biologi, 2017)
This study aims to determine the teaching materials developed worthy of use as a teaching material for tissue culture in SMA Negeri 5 Padangsidimpuan based on BNSP assessment criteria. Knowing the effectiveness of biological teaching materials with Student Centered Learning approaches on tissue culture materials as reading material for students of grade XI IPA SMA / MA effective and improve students biology learning outcomes. This research is research of development of 4D model (four D model) suggested by Thiagrajan et al (1974) with research procedure covering Define, Designe, Develope and Dessiminate. The data obtained in the form of quantitative data validator and qualitative data. The product of this research is tissue culture teaching material for high school / MA students. Based on the results of the study, the average percentage of six validators on the teaching materials of students is 80.69% with the conclusions of the teaching materials worthy of use as teaching materials and this product can be followed by a small revision adding some supporters to optimize the results of the teaching materials by considering the advice and criticism from the validator. Result of questionnaire analysis of student response in general obtained average percentage of 81,24% mean student have been able to comprehend teaching materials that have been developed and effective for use in learning process.